Al-Waḥdah (Unity) in Islamic Law and its Implications for National Integration - Lateef, Abiola Muideen (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Islamic law rests on the precipice of Al-Waḥdah (Unity) which includes unity of the humankind, unity between human being and his environment, unity within the family, unity of the state and society, of government and politics, of economy and culture, and law and policy. Several studies have tended to focus on the negative perception of Islamic law as inimical to national unity while little or no attention has been paid to its cohesiveness and civilizational dialogue with other cultures. Using socio-historical approach, the paper examines the concept of Al-Waḥdah paradigm in Islamic law in Nigerian legal context with a view to understanding the implications concerning national integration. It was discovered that Islamic law had contributed to the integration of Nigeria as a nation in the past and its neglect would not augur well for national integration. This paper therefore, argues that Islamic law has a lot to offer in the national integration of the country especially in the areas of education, economy, socio-psychology, morality and diplomacy. Finally, the paper affirms that the significance of Islamic law transcends religious sphere, and hence, should be allowed to play its role in the national integration of the country. It suggests that for national integration to be achieved in Nigeria, Muslims in the country need to re-orient themselves to the concept of Al-Waḥdah articulated by Islamic law.